Legalitas Donor Mata Dalam Islam: Perspektif Hukum Kesehatan Dan Hukum Islam - Mustafid, Mustafid (Jurnal Fakta Hukum, 2023)
The problem in this study is about the legality of eye donors in Islam in terms of health law and Islamic law. This type of research is library research with a normative approach, while the primary data source uses the Minister of Health Regulation No. 38 of 2016 concerning Organ Transplantation. At the same time, secondary data uses books, journal articles, and others using descriptive data analysis techniques. The results of this paper show that in the health law in Indonesia, it is explained that two human conditions can become donors, namely people who are still alive and people who have died of the brain stem. People who are still alive can only donate one kidney, part of the liver, pancreas, or lung, while people who have died of the brain stem may donate organs, so the authors conclude that eyes may be donated by people who are dying of the brain stem. Meanwhile, according to the perspective of Islamic law regarding eye donors, there are two opinions. First, people who are still alive may not donate their eyes, secondly; people who have died, and the clergy's attitude towards this matter, first; saying it is not permissible because the organs of the body belong to Allah and those who have left them have the right to respect their bodies, second; the opinion that says it is permissible, with the reason that it is a good and commendable deed because the organ can be used by people who need it, rather than being damaged just like that after the body is buried. Humanity's deeds are respected by religion and Eliminate the suffering of others.